176 EXPLORING THE PREVALENCE AND PRESENTATION OF FRAILTY IN AN IRISH EMERGENCY DEPARTMENT – A POINT PREVALENCE STUDY. (25th October 2022) - O'Neill, S; McShane, N; Nelson, C
Abstract: Background: In Ireland, frailty is routinely identified in the Emergency Department (ED), however its prevalence is not well defined. This contrasts with the prevalence of frailty in the older adult population living in the community setting, where the prevalence of frailty has been defined as 14% in the over 65 population and 33% in the 75 and over (TILDA, 2020). The aim of the study is to explore the prevalence and presentation of frailty in the older adult population attending ED of a model 3 hospital in Ireland. Methods: In August 2021, a point prevalence study was undertaken in the ED over 14 days, covering a 24-hour period, applying retrospective documentary and observational data analysis. Measures used to identify frailty included: Think Frailty and Clinical Frailty Scale (CFS) version 2.0. Results: 2, 582 individuals attended ED over a 2-week period. 22% were aged 65 and over, of which, 37.5% were aged 65 – 74 and 62.5% were aged 75 and over. 60% were admitted and 40% were discharged. Of those identified as living with frailty – 24.8% were identified to be living with severe/very severe frailty (CFS 7 – 8); 19.5% with moderate frailty (CFS 6), and 35.66% with mild/very mild frailty (CFS 4 – 5). The majority of those identified at CFS 1 – 3 were aged 65 – 74. The identified frailty syndromes included, polypharmacy (38.5%), reduced mobility (30.3%), falls (20%), dementia (6%), Delirium (5%), Incontinence (0%). Conclusion: The results indicated that 80% of the identified cohort were living with frailty (CFS 4 – 8). Frailty status and advancing age were associated with a longer length of stay in ED and a subsequent admission. Dominant frailty syndromes included polypharmacy and reduced mobility; frailty syndromes such as delirium and incontinence appear to be underrepresented, which may be influenced by the absence of routine identification in the ED.